2010
DOI: 10.1530/eje-09-0850
|View full text |Cite
|
Sign up to set email alerts
|

Risk of spontaneous miscarriage in euthyroid women with thyroid autoimmunity undergoing IVF: a meta-analysis

Abstract: Objective: To investigate whether thyroid autoimmunity (TAI) is associated with increased risk for spontaneous miscarriage in subfertile, euthyroid women undergoing IVF. Design: Meta-analysis of observational studies. Patient(s): Four prospective studies that reported data on 1098 subfertile women undergoing IVF (141 with TAI and 957 controls) were included in the meta-analysis. Main outcome measure: Miscarriage risk ratio (RR). Secondary outcome measures: Clinical pregnancy rate and delivery rate. Result(s): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
2
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 38 publications
3
90
2
8
Order By: Relevance
“…52,53 In a metaanalysis carried out by Toulis et al in 2010 abortus rate was found to be 2 times higher in euthyroid IVF patients with positive thyroid autoimmunity. 54 Revell et al has emphasized in their study that during IVF, in order to increase pregnancy and implantation rates and reduce abortus rate ATA positive patients must be treated even if they are eutyhroid. 55 …”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…52,53 In a metaanalysis carried out by Toulis et al in 2010 abortus rate was found to be 2 times higher in euthyroid IVF patients with positive thyroid autoimmunity. 54 Revell et al has emphasized in their study that during IVF, in order to increase pregnancy and implantation rates and reduce abortus rate ATA positive patients must be treated even if they are eutyhroid. 55 …”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…Positive thyroid autoimmunity is present in about 10% of pregnant women (116,117). Three meta-analyses have demonstrated a positive association between thyroid autoimmunity and both abortion and prematurity (8,116,118), although this association has not been confirmed in another (101).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Three meta-analyses have demonstrated a positive association between thyroid autoimmunity and both abortion and prematurity (8,116,118), although this association has not been confirmed in another (101). Negro et al demonstrated that T 4 treatment in women with TAI significantly decreased the number of miscarriages (94,119).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…On the other hand, a retrospective study by Tierney et al [24] performed in Australia found no difference in preterm deliveries between women who were thyroid antibody positive and women who were thyroid antibody negative.…”
Section: Observationmentioning
confidence: 90%
“…Although many types of antithyroid antibodies have been described, the most common is the group of antibodies directed against various parts of the thyroid peroxidase molecule [24][25][26]. Most pregnant women with abnormally elevated serum levels of thyroid peroxidase antibodies are clinically and biochemically euthyroid, but they may be at increased risk of spontaneous abortion, and preterm delivery and other pregnancy complications [11,27].…”
Section: Observationmentioning
confidence: 99%